2014
DOI: 10.1590/s1517-83822014000400009
|View full text |Cite
|
Sign up to set email alerts
|

Large scale distribution of bacterial communities in the upper Paraná River floodplain

Abstract: A bacterial community has a central role in nutrient cycle in aquatic habitats. Therefore, it is important to analyze how this community is distributed throughout different locations. Thirty-six different sites in the upper Paraná River floodplain were surveyed to determine the influence of environmental variable in bacterial community composition. The sites are classified as rivers, channels, and floodplain lakes connected or unconnected to the main river channel. The bacterial community structure was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Further research has revealed that a positive correlation exists between the concentrations of Chl a and the abundance of Flavobacterium in Jingpo Lake. In previous studies, it was also well-documented that Chl a has a strong correlation with Flavobacterium [ 57 , 58 ]. A similar trend occurs with pH and TP.…”
Section: Discussionmentioning
confidence: 90%
“…Further research has revealed that a positive correlation exists between the concentrations of Chl a and the abundance of Flavobacterium in Jingpo Lake. In previous studies, it was also well-documented that Chl a has a strong correlation with Flavobacterium [ 57 , 58 ]. A similar trend occurs with pH and TP.…”
Section: Discussionmentioning
confidence: 90%
“…The authors have studied Bacteria and Archaea in this environment, correlating the pulses of organic matter with the community variations when the river waters were high or low, and concluded that Archaea was less abundant than Bacteria in all times and seasons sampled [43, 44]. …”
Section: Archaea In Aquatic Environmentsmentioning
confidence: 99%